Non-Muslim Perceptions of Halal Muslim Life Style in Manado City and Its Influence on Social Distance - Amin, Ali; Iqbal Suma, Muhammad; Kusuma Dewi, Subkhani; Mansyur, Zulkifli (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Halal food/drink is food or beverages that do not contain haram food or drink ingredients (especially pork and khamr) according to Islamic law. In Indonesia, consuming halal food is one of the essensial identities of a Muslim, which has recently been strengthened through public regulations. This strengthening of religious identity, especially among the Muslim minority, might create social distance characterized by Muslims’ limiting or avoiding contact with non-Muslims. While previous research found social distance exists in Muslim minorities towards non-Muslims, this research explains the lack of social distance among majority non-Muslims towards minority Muslims. Using mixed quantitative and qualitative methods, through survey, observations and interviews with 50 respondents in Manado, this research found that social distance towards the “strengthening” of halal identity among Muslims is hardly seen among Christian respondents. The fact that Muslims have restrictions on consuming non-halal food, while Minahasa Christians do not have such equal restrictions on consuming Muslim food, confirms the quantitative data. In contrast to Muslims, who have restrictions on consuming non-halal food, Minahasan Christians do not have restrictions on consuming Muslim (halal) food. This study strengthens the argument that the “halal” identity creates social distance in Manado society among Muslims towards others and not vice versa.